Optimal Financial Instruments - ZENDER, JAIME F. (Journal of Finance, 1991)
ABSTRACT Debt and equity are developed as optimal financial instruments in a model where cash flows and control rights are allocated to investors endogenously. When investment decisions must be made by a single party, the debtholder's cash flows are fixed in order to provide the equityholder with efficient incentives for investment. Ownership of control may be transferred to the debtholder to attenuate the impact of asymmetric information, concerning the investment opportunity, on the efficiency of the decision making.